An Overview of Technology Integration in Nigerian Colleges of Education - Garba, Sani Alhaji; Ranjit Singh, Termit Kaur; Mohammad Yusuf, Najeemah; Abu Ziden, Azidah (Universitas Ahmad Dahlan, 2013)
The influence of digital technology in society has made ICT literacy a basic requirement needed by all to survive the challenge of living in the 21st. The education industry is now faced with the challenge of helping learners to acquire this literacy. Coping with this challenge requires breeding teachers’ with high level of proficiency in ICT literacy and competence. This study investigates the readiness of Nigerian Colleges of Education toward breeding social studies teachers with ICT literacy and competence. It is an exploratory conceptual study that is literaturebased (document-based qualitative study approach). The study therefore explore literature to find out the benefit of ICT integration in social studies teacher education; the preparedness of Nigerian Colleges of Education for ICT integration; and the implications of the current state of technology integration on social studies objectives. Findings from this study indicated that, Colleges of education in Nigeria are not readily prepared for effective technology integration; much is still needed in terms of infrastructure and manpower development.